Plan de negocios para la implementación de una planta de procesamiento de pollos en la asociación de productores agropecuarios visión y progreso en el barrio Mollepamba de la parroquia de Nambacola del cantón Gonzanamá de la provincia de Loja - Quito Ramón, Landy Sofía (2015)
This work was created by the need to support farmers' organizations, specifically the Agricultural Producers Association Vision and Progress, thanks to the support of public entities (infrastructure and training), has successfully implemented on their farms farms devoted to raising chickens farmers. But the mystery of what to do once the processing time arises? who to sell? how to do? how much to sell? Despite having facilities for the dressing process, you do not have the minimum equipment necessary to achieve a continuous process and respecting the appropriate treatment should be given to meat. That is why we have seen the need for a business plan for the implementation of a chicken processing plant, and also to complement the production process, it is proposed to add value to the product, through the development of "smoked chicken" that besides lengthen shelf life and facilitate the transport process for marketing, allow you to increase revenue in sales. Thus, in this project a market study is first performed in the area of Loja, and Gonzanamá Catamayo, in order to investigate and determine the market supply, demand and competition. This 100 surveys aimed at the Loja population, the population 15 and 10 Catamayenses population Gonzanamá performed. Subsequently, a chicken slaughtering process is determined by using bibliographic references and a process of making smoked chicken. In determining the latter process three experimental tests are performed naturally smoked chicken, smoked chicken with liquid smoke and smoked chicken using two techniques (natural and liquid). To decide which of the three products is to be documenting a preference test is performed between members of the organization. Then a financial analysis is performed to determine how profitable is the implementation of the plant, for it quotes from local and imported machinery and other items of monetary references framed within the current law are used. Prior to this analysis the business plan itself, which contains information about the mission, vision, definition of products to offer, FODA and FAFODADO strategies, strategies for marketing of products, a production plan is drawn up and organizational structure with the description of the roles and functions of each of the charges